Factors affecting sleep quality in acute coronary syndrome survivors - Susuthi, Pattaranan; Wattanakitkrileart, Doungrut; Pongthavornkamol, Kanaungnit; Dumavibhat, Chatkanok (Chulalongkorn Medical Journal, 2020)
Background: Sleep quality is critical for survivors of acute coronary syndrome (ACS). Poor sleep quality increases the functioning of the sympathetic system while decreasing the functioning of the parasympathetic system. In fact, an increase in coronary calcium and narrowing of arteries are indicators of poorer prognosis, putting the patients at risks of recurrence of ACS. Objectives: The present study aimed to investigate effects of physical activity, perceived angina severity, depression, and fear of dying on sleep quality of ACS survivors. Methods: The sample consisted of 147 ACS patients, both male and female, who were 18 years old and older and diagnosed with ACS and received treatment for no more than one year at the research settings. Data were analyzed descriptive by statistics and multiple regression statistics. Results: Physical activity, perceived angina severity, depression and fear of dying were able to jointly explain 26.6 % of the variances in sleep quality in ACS survivors (R2 = 0.266, P < 0.001). Physical activity and depression were variables found capable of predicting the sleep quality of ACS survivors with statistical significance ( = - 0.300, 0.331, respectively; P < 0.01) Conclusion: Nurses should assess physical activity and depression in ACS survivors to devise plans to manage depression and promote physical activity to enhance sleep quality of ACS survivors.